2019
DOI: 10.1186/s13046-019-1155-6
|View full text |Cite
|
Sign up to set email alerts
|

Xenotropic and polytropic retrovirus receptor 1 (XPR1) promotes progression of tongue squamous cell carcinoma (TSCC) via activation of NF-κB signaling

Abstract: Background Xenotropic and polytropic retrovirus receptor 1 (XPR1), a previously identified cellular receptor for several murine leukemia viruses, plays a role in many pathophysiological processes. However, the role of XPR1 in human cancers has not yet been characterized. Methods Real-time PCR and western blotting assay were used to measure the expression of XPR1 in tongue squamous cell carcinoma (TSCC) tissues. Expression of XPR1 and p65 in clinical specimens was analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…We discovered that the SDGs were mainly enriched in the NF−kappaB signaling pathway and DNA repair by GO and KEGG analyses. Several studies have strongly supported the associations between NF−kappaB signaling pathway and HNC [20][21][22] . Qin Y et.al found the CCL18 (chemokine (C-C motif) ligand 18) could promote the HNSCC malignancy and its level was signi cantly associated with histological grade through regulating the NF−κB signal pathway [20] .…”
Section: Discussionmentioning
confidence: 94%
“…We discovered that the SDGs were mainly enriched in the NF−kappaB signaling pathway and DNA repair by GO and KEGG analyses. Several studies have strongly supported the associations between NF−kappaB signaling pathway and HNC [20][21][22] . Qin Y et.al found the CCL18 (chemokine (C-C motif) ligand 18) could promote the HNSCC malignancy and its level was signi cantly associated with histological grade through regulating the NF−κB signal pathway [20] .…”
Section: Discussionmentioning
confidence: 94%
“…We discovered that the SDGs were mainly enriched in the NF − kappaB signaling pathway and DNA repair by GO and KEGG analyses. Several studies have strongly supported the associations between NF − kappaB signaling pathway and HNC [20][21][22] . Qin Y et.al found that CCL18 (chemokine (C-C motif) ligand 18) could promote the HNSCC malignancy and its level was signi cantly associated with histological grade through regulating the NF − κB signal pathway [20] .…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, the NF − κB inhibitor could reduce the invasion of HNSCC cells [21] . In addition, the NF − κB pathway induced by XPR1 was related to many aspects of TSCC (tongue squamous cell carcinoma), including the tumor grade and patients' prognosis [22] . These studies illuminated the functions of NF − κB signal pathway in the HNSCC malignancy in terms of histological grade.…”
Section: Discussionmentioning
confidence: 99%
“…However, the underlying molecular mechanism remains unknown. It has been reported that the NF‐kB and the ERK MAPK signaling pathways play an important role in the invasion and metastasis of cancers 16‐19 . Hence, western blotting was carried out to preliminarily test the molecular changes in NF‐kB and the ERK MAPK signaling pathways.…”
Section: Resultsmentioning
confidence: 99%